Serum Uric Acid-Lowering Effects of Combined Glycine and Tryptophan Treatments in Subjects with Mild Hyperuricemia: A Randomized, Double-Blind, Placebo-Controlled, Crossover Study - Oshima, Shunji; Shiiya, Sachie; Nakamura, Yasunori (Nutrients, 2019)
We determined the serum uric acid-lowering effects of combined daily supplementation of glycine and tryptophan in patients with mild hyperuricemia using a randomized, double-blind, placebo-controlled, crossover clinical trial design. Japanese healthy adult males and females with mild hyperuricemia (fasting serum uric acid of 6.6–7.9 mg/dL) ingested a powder mixture containing 3.0 g of glycine and 0.2 g of tryptophan or a placebo powder once daily at bedtime for 6 weeks. Combined supplementation with glycine and tryptophan significantly decreased serum uric acid levels (from 7.1 mg/dL to 6.7 mg/dL, p = 0.004) before and after the trial. Serum uric acid concentrations significantly decreased in the subjects supplemented with the amino acid mixture compared with those in placebo-treated subjects (p = 0.028). In addition, the combination treatment with glycine and tryptophan decreased serum triglyceride levels (from 119 mg/dL to 86 mg/dL, p = 0.002). Increased solubility of uric acid caused by urinary pH were likely contributors to the serum uric acid-lowering effects of the amino acid mixture.